BENEFITS OF INQUIRY-BASED INSTRUCTION AS A TEACHING STRATEGY - Nuran Murshudzada (Research Retrieval and Academic Letters, 2023)
Language acquisition can be facilitated by the use of instructional techniques. In Azerbaijan, English is a foreign language, and teachers take a variety of courses to strengthen their professional teaching abilities with advanced methods and techniques that are accepted in all industrialized nations. The language teaching strategies (LTS) are intended for both teachers and students in this task and can direct them toward a better learning path. A teaching strategy called inquiry-based learning encourages pupils to ponder and research issues from the outside world. This method of education is advantageous in many ways and is applicable to many different subject areas. Students can integrate what they are learning in the classroom with the outside world through this style of learning, which frequently involves hands-on activities. It has been demonstrated that inquiry-based learning fosters greater creativity, critical thinking, and problem-solving abilities.